Stability of a sustainable remote area microgrid - Shahnia, Farhad (2017)
© 2016 IEEE.Electrical system of remote areas is usually in the form of a standalone system. Renewable energies are desired to generate all electricity demand in these areas to reduce the cost of electricity production, if available sufficiently. Thereby, the electrical system of those remote areas can be thought as a sustainable microgrid. Larger remote areas may be supplied by multiple independent microgrids, each with a different owner. The occasional power deficiency in these microgrids can be mitigated by importing power from a neighboring microgrid, after their provisional coupling. The stability of the newly generated system should be checked before the coupling to avoid the coupling if instability is to occur. A small signal stability analysis is used in this research for such microgrids. The impact of the number and rating of the sources and loads, as well as the system topology of one microgrid on the stability of the system of coupled microgrids, is assessed through numerical analyses in MATLAB.